Instrument of Creative Thinking Skills in Project Based Learning Physics - Utama, Aldi Setia; Rosidin, Undang; Suyatna, Agus (Universitas Islam Negeri Raden Intan Lampung, 2021)
To identify students’ creative thinking skills, appropriate instrument is needed. This study aimed to produce a valid creative thinking skills instrument. From several relevant studies, they only focus their research on developing skills instruments using a 4-D model approach and problem solving, while this research uses a project-based pursuit approach. The results of the validation of the three validators covering aspects of construction, substance, and language, revealed that the average score of the validation results for the construction aspects was 83% which was considered very valid. The average score of the validation results on the substance aspect is 86% with very valid criteria, and in the language aspect it reaches 85% with very valid criteria. Accordingly, this instrument of creative thinking skills is said to have been qualified with very decent and excellent quality for use in learning in schools to help teachers to assess students’ creative thinking skills.